2000
DOI: 10.3168/jds.s0022-0302(00)75013-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Analysis of Antihypertensive Peptides That Exist Naturally in Gouda Cheese

Abstract: Seven kinds of ripened cheeses (8-mo-aged and 24-mo-aged Gouda, Emmental, Blue, Camembert, Edam, and Havarti) were homogenized with distilled water, and water-soluble peptides were prepared by C-18 hydrophobic chromatography. The inhibitory activity to angiotensin I-converting enzyme and decrease in the systolic blood pressure in spontaneously hypertensive rats were measured before and after oral administration of each peptide sample. The strongest depressive effect in the systolic blood pressure (-24.7 mm Hg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
1
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(205 citation statements)
references
References 16 publications
4
182
1
9
Order By: Relevance
“…Saito et al (2000) and Gómez-Ruiz, Ramos and Recio (2004) obtained casein peptides with similar molar mass molecular weight; nevertheless, they registered no antioxidant effect, as described in our study. They noted, however, antihypertensive properties.…”
Section: Antioxidant Activity Evaluation Of Caprine Casein Hydrolysatesmentioning
confidence: 57%
See 1 more Smart Citation
“…Saito et al (2000) and Gómez-Ruiz, Ramos and Recio (2004) obtained casein peptides with similar molar mass molecular weight; nevertheless, they registered no antioxidant effect, as described in our study. They noted, however, antihypertensive properties.…”
Section: Antioxidant Activity Evaluation Of Caprine Casein Hydrolysatesmentioning
confidence: 57%
“…Another peptides detected in our study were 887, 970 and 978 Da, earlier obtained by Saito et al (2000), Gómez-Ruiz, Ramos and Recio (2004) and Gómez-Ruiz et al (2008) from bovine casein hydrolysates. These peptides demonstrated antihypertensive and antioxidant characteristics.…”
Section: Peptide Profile and Amino Acids Sequencing From Casein Hydromentioning
confidence: 84%
“…The levels of BCM7 and other related BCMs reported in some cheeses are shown in Table 2. In addition to BCM7, BCM5 was found in Brie, Rokpol, Edamski, Gouda, and Kasztelan (Sienkiewicz-Sz»apka et al, 2009), BCM9 (Saito et al, 2000;Toelstede and Hofmann, 2008) and BCM10 in Gouda (Toelstede and Hofmann, 2008) and BCM 11 in Caprino del Piemonte, an Italian goat cheese (Rizzello et al, 2005). In contrast, Muehlenkamp and Warthesen (1996) reported that BCM7 were not detected in Brie and Cheddar.…”
Section: Cheesementioning
confidence: 91%
“…The IC 50 of V-b-casomorphin-9 against ACE was determined to be 325 lM. In the case of V-b-casomorphin-9, Saito et al [30] previously published an IC 50 value of 14.8 lM for b-casomorphin-9 (YPFPGPIPN), which exhibits a structural resemblance to V-b-casomorphin-9 (VYPFPGPIPN). Therefore, we conclude that additional Val at the N-terminal end of V-b-casomorphin-9 increased the IC 50 value almost 22-fold from 14.8 to 325 lM.…”
Section: Antihypertensive Effect and Mechanism Of Ace Inhibitionmentioning
confidence: 99%